2015
DOI: 10.1016/j.jcv.2015.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Direct multiplexed whole genome sequencing of respiratory tract samples reveals full viral genomic information

Abstract: Our study shows that, in a single run, viral pathogens can be detected and characterized, providing information for clinical assessment and epidemiological studies. We conclude that WGS is a powerful tool in clinical virology that delivers comprehensive information on the viral content of clinical samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…Another strategy is to perform shotgun sequencing of nucleic acids isolated from the entire, unseparated clinical sample (i.e., metagenomics). This method has been previously applied to total nucleic acids (RNA and DNA) extracted from clinical samples for viral detection [10][11][12][13]. Although metagenomic sequencing of total nucleic acids can detect viruses, its feasibility is highly dependent on the level of virus present in the sample and the amount of host cell nucleic acid present, which can in turn demand high levels of sequence depth for virus detection.…”
Section: Introductionmentioning
confidence: 99%
“…Another strategy is to perform shotgun sequencing of nucleic acids isolated from the entire, unseparated clinical sample (i.e., metagenomics). This method has been previously applied to total nucleic acids (RNA and DNA) extracted from clinical samples for viral detection [10][11][12][13]. Although metagenomic sequencing of total nucleic acids can detect viruses, its feasibility is highly dependent on the level of virus present in the sample and the amount of host cell nucleic acid present, which can in turn demand high levels of sequence depth for virus detection.…”
Section: Introductionmentioning
confidence: 99%
“…A third study demonstrated that HTS could be used to detect a pathogen (rhinovirus C) in a sample from a child with respiratory symptoms in which no virus had been detected by PCR. 26 Taken together, these data show that in some cases HTS could be advantageous compared with PCR assays, but sensitivity of sequencing can be a limitation.…”
Section: High-throughput Sequencing In the Clinic Sequencing Assays Cmentioning
confidence: 84%
“…Additionally, the predominant genera identified included HRSV, influenza virus A and HRV, whereas influenza A and HRV represented a small proportion of viral reads in the present analysis. Zoll et al [22] reported that HRV, TTV and TTMV were frequently detected in children and that viral populations were less complicated than those found in children from Beijing. The only viral metagenomic research on respiratory samples was reported by Yang et al [17] in China, in which only 0.05% of the sequences were virally derived.…”
Section: Discussionmentioning
confidence: 99%